Older Adults with Multi-Morbidity: Medication Management Processes and Design Implications for Personal Health Applications - Haverhals, Leah M; Lee, Courtney A; Siek, Katie A; Darr, Carol A; Linnebur, Sunny A; Ruscin, J Mark; Ross, Stephen E (JMIR Publications, 2011)
BackgroundOlder adults often have multiple chronic problems requiring them to manage complex medication regimens overseen by various clinicians. Personal health applications (PHAs) show promise assisting in medication self-management, but adoption of new computer technologies by this population is challenging. Optimizing the utility of PHAs requires a thorough understanding of older adults' needs, preferences, and practices. ObjectiveThe objective of our study was to understand the medication self-management issues faced by older adults and caregivers that can be addressed by an electronic PHA. MethodsWe conducted a qualitative analysis of a series of individual and group semistructured interviews with participants who were identified through purposive sampling. ResultsWe interviewed 32 adult patients and 2 adult family caregivers. We identified 5 core themes regarding medication self-management challenges: seeking reliable medication information, maintaining autonomy in medication treatment decisions, worrying about taking too many medications, reconciling information discrepancies between allopathic and alternative medical therapies, and tracking and coordinating health information between multiple providers. ConclusionsThis study provides insights into the latent concerns and challenges faced by older adults and caregivers in managing medications. The results suggest that PHAs should have the following features to accommodate the management strategies and information preferences of this population: (1) provide links to authoritative and reliable information on side effects, drug interactions, and other medication-related concerns in a way that is clear, concise, and easy to navigate, (2) facilitate communication between patients and doctors and pharmacists through electronic messaging and health information exchange, and (3) provide patients the ability to selectively disclose medication information to different clinicians.